A new genus and species of clearwing moths (Lepidoptera: Sesiidae) from South Sudan - Gorbunov, Oleg G.; Gurko, Vladimir O. (Zootaxa, 2017)
A new clearwing moth genus and species is described and illustrated from South Sudan: Lolibaia salimi gen. nov. et sp. nov.. This is the first record of the family Sesiidae from that country. The holotype is deposited in the collection of the A.N. Severtsov Institute of Ecology and Evolution of the Russian Academy of Sciences, Moscow, Russia.